SIFAT FISIK TANAH PADA HUTAN PRIMER, AGROFORESTRI DAN KEBUN KAKAO DI SUBDAS WERA SALUOPA DESA LEBONI KECAMATAN PAMONA PUSELEMBA KABUPATEN POSO - Tolaka, Wilman; Wardah, Wardah; Rahmawati, Rahmawati (Universitas Tadulako, 2013)
Land use and forest harvesting (timber and non-timber) could lead to the opening of ground cover. This activity would lead to disruption of physical properties, chemical and biological soil, especially in the top soil.The purpose of this study was to determine the physical properties of soil on different types of land use, i.e in primary forest, agroforestry and cocoa plantation in the sub-watershed Wera Saluopa which is part of the sub-watershed area of Maraoa Koronjongi. The study was conducted from May till July 2013, on the various types (primary forest, cocoa plantation and agroforestry land) for soil sampling, laboratory analysis of soil samples and analysis of data. Study site selection was purposive sampling where Saluopa Wera Sub-watershed, in the village of Leboni, District Puselemba Pamona, Poso Regency of Central Sulawesi.The results showed that the physical properties of the soil at various types of land use in the sub-watershed of WeraSaluopa have sandy loam soil texture, soil permeability varies from very slow (primary forest) to very fast (agroforestry), soil porosity from 49.93% (primary forest) to 54.04% (cocoa plantation) with high bulk density â‰¥ 1.0. Hence, the highest of soil organic matter was in primary forest(7.09) followed by cocoa plantation (5.86) and agroforestry land (4,12). Keyword : the physical properties, primary forest, Agroforestry, cacao plantation